Gynecological Adverse effects of Tamoxifen Treatment to Hormone Receptor Positive Breast Cancer Female Patients: Gynecological Effects of Tamoxifen in Hormone Receptor Positive Breast Cancer Patients - Raza, Uzma; Khanam, Aziza; Iftikhar, Ali; Sadat, Ayman; Rizwan, Sidra; Sheikh, Aminuddin (Pakistan Journal of Health Sciences, 2025)
Tamoxifen, an oral synthetic selective estrogen modulator, has been widely used as an anti-cancer drug for over 50 years. Tamoxifen increases disease free survival and overall survival rates, when given as an adjuvant but many patients experience side effects which reduces quality of life. The present study investigates the adverse effects of tamoxifen in hormone receptor–positive breast cancer patients. Objectives: To investigate the Adverse effect of tamoxifen treatment on hormone receptor positive breast cancer patient. Methods: The longitudinal cohort study was conducted at Al-Tibri Medical College with collaboration of Liaquat National Hospital Karachi from March 2019 to Sep 2023. The study included 135 premenopausal women with hormone receptor–positive breast cancer. After surgery and chemotherapy, all received tamoxifen 20 mg/day for five years and were evaluated every six months for four years. Results: A total of 135 premenopausal hormone receptor–positive breast cancer patients were studied. Mean age was 44.6 years, and 79% had children. Endometrial thickness increased from 5.0 mm before treatment to 9.3 mm after 48 months of Tamoxifen (p<0.05). Common adverse effects included vaginal discharge (36%), hot flashes (19%), and rash pigmentation (14%). D and C and Pap smear showed mostly benign or inflammatory changes. Long-term Tamoxifen use was linked to increased endometrial thickness and mild gynecological side effects. Conclusion: Tamoxifen showed mild, tolerable side effects and histopathological changes but effectively reduced metastasis, supporting its use with regular endometrial monitoring.